INTEGRATION OF EDUCATIONAL PHILOSOPHY AND HUMANISTIC PSYCHOLOGY IN JUNIOR HIGH SCHOOL STUDENTS’ CHARACTER FORMATION - Risanti, Yulia; Rahman, Maulana Fathur; Sugiarti, Lucia Rini; Suhariadi, Fendy (STKIP Citra Bakti, 2026)
Character education at the junior high school level is a crucial foundation for students’ moral, emotional, and social development. During early adolescence, students experience significant psychological changes that require educational approaches emphasizing human values and personal meaning. This study aims to examine the integration of educational philosophy and humanistic psychology as a conceptual framework for strengthening students’ character formation. This research employed a qualitative literature review method by analyzing books and peer-reviewed journal articles related to educational philosophy, humanistic psychology, and character education published within the last decade. The results indicate that the integration of educational philosophy and humanistic psychology supports character development through meaningful learning experiences, democratic teacher–student relationships, and the cultivation of values such as responsibility, autonomy, empathy, and respect. This integrative framework is important for establishing holistic education that balances academic achievement and character maturity.